Jamaica : Staff Report for the 2014 Article IV Consultation and Fourth Review under the Extended Arrangement under the Extended Fund Facility and Request for Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that a gradual economic recovery appears to be under way in Jamaica. Growth is estimated at 0.9 percent in FY2013/14, as mining, agriculture, and tourism picked up. Recorded unemployment remains high, but fell from 16 percent to 13.5 percent (in seasonally adjusted terms) from April 2013 to January 2014. Inflation declined to 7.6 percent (year over year) at end-April, as the impact of the ongoing depreciation of the exchange rate was countered by weak domestic demand. Growth is projected to reach almost 1 1\2 percent in 2014-2015, as the negative fiscal impulse comes to an end.